A FORMAÇÃO DE ESQUEMAS EMERGENTES SIGNIFICATIVOS COMO FONTE DE COMPREENSÃO LEITORA: UMA ABORDAGEM CONEXIONISTA - Nunes, Elizabete Kuczynski (Revista Liberato, 2013)
The present article presents contributions from the connectionist paradigm in order to explain the relation between brain processes and cognitive activities in the field of cognitive science such as emergent brain schemata formation and reading comprehension using computational simulation. Similar to a computer artificial neural network, a reader’s brain processes and stores information along several interconnected units producing generalizations and abstractions working on a parallel distributed process of information. The reader processes the words from a text integrating new information to existing knowledge, setting up new connections. In fact, distributed, fragmented and widespread concepts are used to codify thoughts and personal experiences. Searching for a meaningful synthesis, the engrams are indexed to explicit, implicit and ultraplicit information, which are modified by the use of dynamic ad hoc configurations. Cognitive processes and operations such as cognitive and metacognitive strategies form syntactic, semantic and phonological knowledge are taken from the text itself. Understanding a text means to form a meaningful synthesis when the brain schemata are organized, elaborated and recalled on a visual image of the whole context.